Self-help and help-seeking for communication disability in Ghana: implications for the development of communication disability rehabilitation services. - Wylie, Karen; McAllister, Lindy; Davidson, Bronwyn; Marshall, Julie; Amponsah, Clement; Bampoe, Josephine Ohenewa (2017)
BACKGROUND: In low and middle-income countries, such as Ghana, communication disability is poorly recognised and rehabilitation services for people with communication disability are limited. As rehabilitation services for communication disability develop, and the profession of speech-language pathology grows, it is important to consider how services can most appropriately respond to the needs and preferences of the community. Understanding the ways in which people currently self-help and seek help for communication disability is central to developing services that build on existing local practices and are relevant to the community. METHODS: A qualitative descriptive survey was used to explore likely self-help and help-seeking behaviours for communication disability, in Accra, Ghana. The survey required participants to describe responses to hypothetical scenarios related to communication disability. A mix of theoretical sampling and convenience sampling was used. Qualitative content analysis was used to analyse data and develop categories and subcategories of reported self-help behaviours and sources of help and advice for communication disability. RESULTS: One hundred and thirty-six participants completed the survey. Results indicated that community members would be likely to engage in a variety self-help strategies in response to communication disability. These included working directly with a person with a communication disability to attempt to remediate a communication impairment, altering physical and communication environments, changing attitudes or care practices, educating themselves about the communication disability, providing resources, and responding in spiritual ways. Participants indicated that they would seek help for communication disability across a range of sectors - including the Western healthcare, religious, and traditional sectors. CONCLUSIONS: Understanding existing community actions to self-help and help-seek may allow emerging communication rehabilitation services, including the profession of speech-language pathology, to build on existing community practices in resource-limited contexts such as Ghana.